Tingkat Keparahan Penyakit pada Daun Mangga (Mangifera indica) Menggunakan Software Imagej dan Plantix serta Kultur Bakteri pada Nutrient Agar (NA) - Imam Rosadi; Linda Oktavianingsih; Cici Lis Qurrotun Ayuni; Muhammadiyah Muhammadiyah; Adelia Putri Aulia; Desinta Amelia Putri Juhri; Iska Puspa Dewi; Sheny Soviana (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine the level of severity on mango (Mangifera indica) leaves. The methods used in this research are identifying disease symptoms using the Plantix application, measuring the severity of leaves using ImageJ software, and culturing bacterial cells on Nutrient Agar (NA). The sample uses 5 leaves and 3 different location points. The research results show that the data obtained from ImageJ software shows the level of severity with an average percentage, namely at location point A it is 1.98%, location point B is 1.18%, and location point C is 2.31%. Based on the results of bacterial cell culture, isolates were obtained with the characteristics, a) shape, namely round; b) the edge line, namely the whole; c) high, that is, convex; d) size, namely medium; e) color, namely colorless; f) texture, namely soft; g) appearance i.e. shiny. Based on the known disease symptoms on mango leaves, mango black bacterial spot disease was identified which was caused by the bacteria Xanthomonas citri pv. mangiferaeindicae. In conclusion, the data obtained from ImageJ software shows that the highest level of severity is at location point C and the lowest level of severity is at location point B. Keywords: Leaves, ImageJ, Mango, Plantix, Xanthomonas